Ecological cross compliance promotes farmland biodiversity in Switzerland. Issue 5 (7th July 2008) - Aviron, Stéphanie; Nitsch, Heike; Jeanneret, Philippe; Buholzer, Serge; Luka, Henryk; Pfiffner, Lukas; Pozzi, Stefano; Schüpbach, Beatrice; Walter, Thomas; Herzog, Felix
Abstract : In ecological cross compliance, farmers have to meet environmental standards in order to qualify for area‐related direct payments. Because this is a strong financial incentive, cross compliance is a potentially powerful policy instrument. We monitored the effectiveness of cross compliance in promoting biodiversity on grassland and on arable land in Switzerland over 8 years. We observed measurable benefits for flora, butterflies, ground beetles, and spiders, in terms of species numbers and/or community composition. However, populations of threatened species showed no signs of benefit. While cross compliance has been in force in Switzerland for almost a decade, it has only recently been introduced in the neighboring European Union. We argue that – provided the environmental standards relating to biodiversity are increased in the future –common farmland biodiversity could be enhanced at the continental scale under cross compliance. The Swiss example shows that appropriate cross‐compliance standards benefit farmland biodiversity at field and farm scales, while the conservation of threatened species needs to be addressed by specific programs, acting at the scale of agricultural landscapes.